The Solanum lycopersicum WRKY3 Transcription Factor SlWRKY3 Is Involved in Salt Stress Tolerance in Tomato - Hichri, Imène; Muhovski, Yordan; Žižková, Eva; Dobrev, Petre I.; Gharbi, Emna; Franco-Zorrilla, Jose M.; Lopez-Vidriero, Irene; Solano, Roberto; Clippe, André; Errachid, Abdelmounaim; Motyka, Vaclav; Lutts, Stanley (Frontiers in Plant Science, 2017)
Salinity threatens productivity of economically important crops such as tomato (Solanum lycopersicum L.). WRKY transcription factors appear, from a growing body of knowledge, as important regulators of abiotic stresses tolerance. Tomato SlWRKY3 is a nuclear protein binding to the consensus CGTTGACC/T W box. SlWRKY3 is preferentially expressed in aged organs, and is rapidly induced by NaCl, KCl and drought. In addition, SlWRKY3 responds to salicylic acid, and 35S::SlWRKY3 tomatoes showed under salt treatment reduced contents of salicylic acid. In tomato, overexpression of SlWRKY3 impacted multiple aspects of salinity tolerance. Indeed, salinized (125 mM NaCl, 20 days) 35S::SlWRKY3 tomato plants displayed reduced oxidative stress and proline contents compared to WT. Physiological parameters related to plant growth (shoot and root biomasss) and photosynthesis (stomatal conductance and chlorophyll a content) were retained in transgenic plants, together with lower Na+ contents in leaves, and higher accumulation of K+ and Ca2+. Microarray analysis confirmed that many stress-related genes were already up-regulated in transgenic tomatoes under optimal conditions of growth, including genes coding for antioxidant enzymes, ion and water transporters, or plant defense proteins. Together, these results indicate that SlWRKY3 is an important regulator of salinity tolerance in tomato.